Impact of onabotulinumtoxinA on quality of life and practical aspects of daily living: A pooled analysis of two randomized controlled trials. (22nd September 2015) - Everaert, Karel; Gruenenfelder, Jennifer; Schulte‐Baukloh, Heinrich; Egerdie, Russell B; Khalaf, Kristin; Joshi, Manher; Ni, Quanhong; Sussman, David
Abstract : Objective: To evaluate the impact of onabotulinumtoxinA on individual domains of the quality of life questionnaires in a pooled analysis of two phase 3 trials in overactive bladder patients with urinary incontinence who were inadequately managed by ≥1 anticholinergic. Methods: Patients received intradetrusor injections of onabotulinumtoxinA 100U ( n  = 557) or placebo ( n  = 548). The proportions of patients with a positive response (condition "greatly improved" or "improved") on the Treatment Benefit Scale, and changes in Incontinence Quality of Life scores and King's Health Questionnaire domain scores were analyzed in the overall population and subgroups with clean intermittent catheterization use and urinary tract infection status during the first 12 weeks of treatment. Responses to individual King's Health Questionnaire items were also assessed. Results: Significantly greater proportions of onabotulinumtoxinA‐treated patients achieved positive Treatment Benefit Scale response versus placebo (61.8% vs 28.0%; P  < 0.001). OnabotulinumtoxinA showed significantly greater improvements versus placebo in Incontinence Quality of Life total (22.5 vs 6.6), Incontinence Quality of Life subscale scores and all domains of the King's Health Questionnaire. Notably, a similar trend was observed regardless of clean intermittent catheterization/urinary tract infection status. Additionally, onabotulinumtoxinA resulted in significantly greater improvements than the placebo in practical aspects of patients daily lives, including pad use, need to change undergarments, sleep, relationship with partner and work life/daily activities. Conclusion: In overactive bladder patients with urinary incontinence, onabotulinu‐mtoxinA 100U demonstrated significant improvements across the individual domains of the quality of life questionnaires, regardless of clean intermittent catheterization or urinary tract infection status, and provided a positive impact on practical aspects of patients' daily lives.